Evaluation of novel synthetic TLR7/8 agonists as vaccine adjuvants. Issue 36 (5th August 2016) - Smith, Alyson J.; Li, Yufeng; Bazin, Hélène G.; St-Jean, Julien R.; Larocque, Daniel; Evans, Jay T.; Baldridge, Jory R.
Highlights: Seven TLR7/8 agonists were synthesized and analyzed for their adjuvanting capacity. Agonists stimulated cytokine production and matured both mDCs and pDCs. The oxoadenine compounds were more potent than the imidazoquinolines. An oxoadenine compound augmented the adaptive immune response to antigen in pigs. Abstract: Small-molecule adjuvants that boost and direct adaptive immunity provide a powerful means to increase the effectiveness of vaccines. Through rational design several novel imidazoquinoline and oxoadenine TLR7/8 agonists, each with unique molecular modifications, were synthesized and assessed for their ability to augment adaptive immunity. All agonists bound human TLR7 and TLR8 and induced maturation of both human mDCs and pDCs. All agonists prompted production of type I interferon and/or proinflammatory cytokines, albeit with varying potencies. In most in vitro assays, the oxoadenine class of agonists proved more potent than the imidazoquinolines. Therefore, an optimized oxoadenine TLR7/8 agonist that demonstrated maximal activity in the in vitro assays was further assessed in a vaccine study with the CRM197 antigen in a porcine model. Antigen-specific antibody production was greatly enhanced in a dose dependent manner, with antibody titers increased 800-fold compared to titers from pigs vaccinated with the non-adjuvanted vaccine. Moreover, pigs vaccinated with antigen containing the highest dose of adjuvant promoted a 13-fold increase in the percentage of antigen-specific CD3 + /CD8 + T cells over pigs vaccinated with antigen alone. Together this work demonstrates the promise of these novel TLR7/8 agonists as effective human vaccine adjuvants.